Testing long-run neutrality of money in a developing economy - Habibullah, Muzafar Shah; Puah, Chin Hong; Mohamed, Azali (2002)
The purpose of the present paper is to determine the long-run neutrality of money in a developing economy - Malaysia - using the Fisher and Seater (1993) approach. Since most of the earlier studies on long-run neutrality (LRN) have been tested on the developed countries, the present study adds to the current literature by providing evidence on LRN from the perspective of a developing country. Furthermore, in this study, not only we test LRN on the aggregate national output, but we also test LRN using disaggregate output. These disaggregate output are namely, the output of agriculture, manufacturing and services sectors. Generally, we found that narrow money M1 does not matter in Malaysia for the sample period, 1973: 1 to 1999:4. The output data at both aggregate and disaggregate sectors support the long-run neutrality of money in Malaysia. This implies that permanent changes in narrow money do not lead to changes in real output. This would suggest that the growth of money supply M1 is not the prime mover for the Malaysia's economic growth during the period under study.